Optimization of amylase production using response surface methodology from newly isolated thermophilic bacteria - Sobia Sharif; Asad Hussain Shah; Anila Fariq; Sammyia Jannat; Sajida Rasheed; Azra Yasmin (Heliyon, 2023)
Present study was aimed at screening and characterizing thermostable amylase-producing bacteria from water and sediment samples of unexplored hot spring of Tatta Pani Kotli Azad Kashmir. Four thermophilic isolates were characterized on morphological, biochemical, physiological basis and were authenticated by molecular analysis. By 16S rDNA sequencing, isolates were identified as Anoxybacillus mongoliensis (MBT001), Anoxybacillus flavithermus (MBT002), Bacillus (MBT004). Among all identified strains, MBT003 showed maximum homology with both Anoxybacillus mongoliensis and Anoxybacillus flavithermus. Amylase activity was analyzed qualitatively in starch agar and quantitatively by DNS method. The optimal enzyme production was observed and authenticated by Response Surface Methodology at 7 pH, 70 °C, 1.25% substrate concentration, 300 μL of inocula volume after 48 h of incubation. Optimum amylase activity (4.4 U/mL) and stability (3.3 U/mL) was observed with 1.5% soluble starch at 70 °C. Maximum activity (3.7 U/mL) and stability (1.5 U/mL) was found at pH 8. Enzyme activity was increased in the presence of MgSO4 and CaCl2. Amylase was stable with surfactants and commercial detergents for 30 min. Supplementation of the enzyme with commercial detergent improved the washing ability of the detergent. This investigation has revealed that these thermostable bacteria are excellent source of amylase which can be used commercially for generating economic activity on sustainable basis.